RETRACTED: The interconnection between the emotional state and the level of development of logical thinking of children of preschool senior age - Kozedub Anastasiya; Dolitskay Itamirel; Kachan Yuliya (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001